Project management in product development: leadership skills and management techniques to deliver great products - Ellis, George (Elsevier, 2016)
Project Management in Product Development: Leadership Skills and Management Techniques to Deliver Great Products is written for new and aspiring project managers in product development. Although texts on project management are common, the material presented here is unique, instead focusing on product development, a challenging segment of project management because of the high level of uncertainty, the need for a robust set of problem-solving techniques, and a demand for broad cross-functional teams.